A critical exploration of professional jurisdictions and role boundaries in inter-professional end-of-life care in the community. (December 2020) - Standing, Holly; Patterson, Rebecca; Dalkin, Sonia; Exley, Catherine; Brittain, Katie
Highlights: Sharing of ACP information between professional groups is inadequate. End-of-life care operates within a hierarchy. Care homes and paramedics in particular feel that their expertise is undervalued. Implementation of ICT innovations such as an EPaCCS may reinforce hierarchies. Abstract: This article critically examines how professional boundaries and hierarchies influence how end-of-life care is managed and negotiated between health and social care professionals. Our findings suggest there is uncertainty and lack of clarity amongst health and social care professionals regarding whose responsibility it is to engage, and document, the wishes of patients who are dying, which can lead to ambiguity in treatment decisions. We go on to explore the potential role of a new electronic system, designed to facilitate information sharing across professional boundaries, in shaping and bridging professional boundaries in the delivery of end-of-life care. We highlight potential negative impacts that may arise when health and social care groups are permitted varying levels of access to the system, and how this may be seen to reflect the value placed on their role in end-of-life care.